PERENCANAAN RUANG PARKIR PADA GEDUNG REKTORAT UNIVERSITAS HALUOLEO - Rachmat Sofyan; Try Sugiyarto Soeparyanto; Mappa Nasrun (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2019)
Abstract The increase in the number of employees, lecturers and students accompanied by an increase in the number of vehicle users as a mode of transportation in the campus of the Halu Oleo University Rector caused serious parking problems. The high level of vehicle ownership raises a discrepancy between the availability of parking lots and the number of vehicles that will use the parking area. This study aims to determine the characteristics of parking in the Halu Oleo University Rectorate and to determine the amount of parking area requirements in the coming year and for parking area planning refers to the Parking Space Unit (SRP). Based on the results of data analysis from research conducted for 2 days, it was shown that for the planning of the parking area at the Halu Oleo University Rectorate, parking lots for two-wheeled vehicles and four-wheeled vehicles would be added to accommodate the vehicles planned for the next 5 years.  Abstrak Peningkatan jumlah Pegawai, Dosen dan Mahasiswa yang di sertai dengan peningkatan jumlah pengguna kendaraan sebagai moda transportasi dikampus Rektorat Universitas Halu Oleo menimbulkan masalah parkir yang serius. Tingkat kepemilikan kendaraan yang cukup besar menimbulkan ketidak sesuaian antara ketersediaan lahan parkir dengan jumlah kendaraan yang akan mengunakan areal parkir.Penelitian ini bertujuan untuk mengetahui karakteristik parkir di Rektorat Universitas Halu Oleo serta untuk mengetahui jumlah kebutuhan lahan parkir pada tahun mendatang dan untuk perencaaan area parkir mengacu pada Satuan Ruang Parkir (SRP). Berdasarkan hasil analisa data dari penelitian yang di lakukan selama 2 hari menunjukan bahwa untuk perencanaan area parkir di Rektorat Universitas Halu Ole o akan di lakukan penambahan petak parkir untuk kendaraan roda dua dan kendaraan roda empat agar dapat menampung kendaraan yang telah di rencanakan untuk 5 tahun kedepan.